Disriminative Policy of The Prohibition To Hold Land Ownership For Chinese -Indonesian In Yogyakarta - Wasisto, Muhammad Adiz (PARAPOLITIKA: Journal of Politics and Democracy Studies, 2023)
Chinese-Indonesians who live in Yogyakarta can no longer possess land ownership legally since the Instructions of the Head of the Special Region of Yogyakarta Number K.898 Year 1975 came into effect. Surprisingly, the discrimination finds its root even before the creation of the nation state of Indonesia. Dutch colonial government is the first authority to initiate such discriminative policy to attenuate Chinese, Arabs, and Indians economic influence in the region and monopolize economic assets above the land. This ethnocentric legal norm permeates and continues its influence in Yogyakarta until now. This paper demonstrates that the instruction as the legal basis in prohibiting Chinese-Indonesians to enjoy land ownership is discriminative. Thus, it is against the legal norms that are applicable in Indonesia. Indonesian legal system treats its citizen equally and does not endorse an ethno-nationalist view that discriminate particular ethnicities. In addition, this paper demonstrates that the instruction cannot be classified as a law, according to legal procedure in Indonesia, therefore renders it unlawful. Lastly, this paper also demonstrates that the instruction is ineffective to serve its purpose because there are many legal loopholes and practices that can avoid its provision.